Pengenalan Konsep Asta Kosala-Kosali Pada Bade Di Bali Berbasis Multimedia Interaktif - Pandawana, I Dewa Gede Agung; Sedhana, Ida Bagus Gede Mertha (Jurnal Sistem Informasi dan Komputer Terapan Indonesia (JSIKTI), 2020)
Asta Kosala Kosali is one of the Balinese local materials in Balinese traditional building lessons. Asta Kosala Kosali is also used in the concept of making Bade, where the concept of measuring Bade is based on the measurements contained in Asta Kosala Kosali. As time goes by, there are still many people who do not know or understand the rules of Asta Kosala Kosali, so the standard Balinese building will gradually diminish in the future. Therefore interactive learning information media can help the community in the process of delivering material that is deemed indispensable and as a supporting medium for Asta Kosala Kosali and Bade materials.In making this interactive media the writer uses Coreldraw X7 software for character creation in the learning media, then for the animation process, button creation, and backsound giving is done using the Adobe Flash CS 6 application. This information media has been tested by distributing questionnaires to the community as many as 30 people, with the aim of finding out how feasible this application can be used. From the results of the questionnaires that have been distributed, it was found that 97% of the people stated that it was very good with the introduction of information media for the introduction of Bade in Bali based on interactive multimedia as a learning information medium.